Penggunaan Portal Berbasis Web SIAP SIJOLI untuk Administrasi Kesiswaan: Studi Kasus MAN 1 Jepara - Iffatul Izza Sufiana; Santi Andriyani (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to determine the implementation of web-based student administration management at MAN 1 Jepara. The background of SIAP SIJOLI was the high number of late students and unexcused absences. SIAP SIJOLI, a website that has been in use for four years with hosting, provides features for nine user accounts, including admin, counseling team, order team, boarding administrator, achievement team, Madrasah head, deputy Madrasah head, and homeroom teacher. The focus of this research is the features in the homeroom teacher and order team accounts. Through qualitative methods, including in-depth interviews with teachers, administrative staff, and the IT team, as well as direct observation, this study analyzed the use of SIAP SIJOLI. Data analysis was conducted through data reduction, narrative presentation, and data triangulation. The results showed that the implementation of SIAP SIJOLI significantly improved administrative efficiency and effectiveness. The order team's recording time was reduced from 3.5 hours to automatic, and the average tardy student decreased from 50-60 students to 5-10 students per day, indicating an increase in efficiency and effectiveness of around 85-90%. SIJOLI READY brought positive changes at MAN 1 Jepara.